Purwarupa Sistem Integrasi Metadata Foto Udara Dengan Data Sistem ADAHRS - Raden Sumiharto; Intan Nur Fadliilah (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2016)
This research was done by implementing aerial photographs metadata integrated system with ADAHRS data system. Photos and ADAHRS data were taken along using the camera and ADAHRS devices were installed on UAV. Data were taken from ADAHRS consisted of date, time, air speed, GPS latitude-longitude, altitude, temperature, air pressure, roll, pitch, and yaw.The method in the system included custom tag configuration, extracted metadata, the synchronisation and integrated data between ADAHRS and photo metadata. Configuration, extraction and integration process were done using ExifTool. Datestamp and timestamp in photo metadata and ADAHRS data were used as a parameter of integrating data on synchronisation.The systematical experiment was done by test on the effect of image resolution and number of photos to the duration of the whole process. This system was able to integrate ADAHRS data from image resolution, were 230 pixels x 1536 pixels, 1920 pixels x 1080 pixels, 1280 pixels x 720 pixels, and 848 pixels and 480 pixels. Amount of time average of process were 3,936 seconds/100 photos, 7,454 seconds/200 photos, 11,156 second/300 photos, 14,740 seconds/400 photos, and 18,460 seconds/500 photos. This system can be able to make a backup from extended version and retain the originality of photo metadata.